O movimento dos trabalhadores rurais sem-terra no Ceará: um novo movimento social? - Maciel, Elda Maria Freire (2000)
This research intends to characterize MST(Movimento dos Trabalhadores Rurais Sem Terra) through their formative as new social movement. The main aim of this research is contribute in the political formation of their social fighters. To reach our aim, we intend to understand such movement through the discourse of their participants, as well as their socialization in the daily fight to reach agrarian reformoWith this struggle, they extract an educational character, that is, a way to form new consciences. Our work is essentially descriptive and the methodology reveals a Case Study, whose unity of research is the Direction of State Movement. We opted to work whit ten directors as subjects of the semistructured interviews. The analysis is supported by categories which lead us to discuss the relation au ship between the theoretical references and the data which were collected in the empirical field. We conclude that MST characterizes a new social movement, however it runs in a perspective to go up the conception that are attributed to the movements which are recognized as new social movements.